The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/rs12071176
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Cotton Stem Water Potential using Sentinel-2 Imagery

Abstract: Monitoring cotton status during the growing season is critical in increasing production efficiency. The water status in cotton is a key factor for yield and cotton quality. Stem water potential (SWP) is a precise indicator for assessing cotton water status. Satellite remote sensing is an effective approach for monitoring cotton growth at a large scale. The aim of this study is to estimate cotton water stress at a high temporal frequency and at a large scale. In this study, we measured midday SWP samples accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…This is because green plants have strong absorption in the red (R) band and strong reflection in the NIR band. Some studies suggest that red edge and NIR bands are important in crop research [51,52]. However, it is worth mentioning that the value of the spectral reflectance curve here was the average value obtained in many sample points.…”
Section: Spectral Bandsmentioning
confidence: 81%
See 1 more Smart Citation
“…This is because green plants have strong absorption in the red (R) band and strong reflection in the NIR band. Some studies suggest that red edge and NIR bands are important in crop research [51,52]. However, it is worth mentioning that the value of the spectral reflectance curve here was the average value obtained in many sample points.…”
Section: Spectral Bandsmentioning
confidence: 81%
“…This is because green plants have strong absorption in the red (R) band and strong reflection in the NIR band. Some studies suggest that red edge and NIR bands are important in crop research [51,52]. However, it is worth mentioning that the value of the spectral reflectance curve here was the average value obtained in many sample points In the image, the actual reflectance value of each sample point fluctuated up and down In a particular band, the range of reflectance values for different crops overlapped.…”
Section: Methodsmentioning
confidence: 89%
“…Reflectance in the visible and SWIR bands was found to be positively correlated with Ψstem, despite increasing reflectance in the SWIR range being commonly found to be strongly correlated with a decrease in leaf water content [79]. However, a negative slope value was also found for SWIR bands in a study conducted on cotton [80]; furthermore, in grapevines, it was found that the slope of the linear model relating Ψstem with B8a and B11 can be negative for Ψstem values > −0.70 MPa and positive for Ψstem < −0.90 MPa [81]. According to our results, Ψstem values lower than −0.90 MPa were found from DOY 201 (July 20) to DOY 234 (August 22, end of the field measurement); this corresponds, in the study area, to the typically warmer summer period.…”
Section: Discussionmentioning
confidence: 78%
“…Remotely sensed data contain rich information on the characteristics of the land surface. A feature space of more than a few dozens to even hundreds of dimensions could be created from the electromagnetic radiation (EMR) that is recorded at different wavelengths, the texture of the spectral bands, and the intra-annual/inter-annual temporal trajectory from the time series observations, which could be further used to determine the land cover based on image classification (Gómez et al, 2016;Pouliot and Latifovic, 2016) or to estimate the biophysical/ biochemical parameters based on machine learning or regression from empirical models (Garbulsky et al, 2011;Lin et al, 2020;Verrelst et al, 2015). Recently, the deep-learning-based approaches, particularly Convolutional Neural Network (CNN), have shown better performance in land cover classification compared to the traditional machinelearning-based methods (Kussul et al, 2017;Liu et al, 2021b;Pouliot et al, 2021), and are capable of incorporating the spatial domain of the remote sensing data by automatically extracting a suitable representation of the remote sensing data through a hierarchy of spatial filters at different sizes, which avoids the feature creation and selection processes that most traditional machine learning methods require in advance for preparation of the classification predictors (Molinier et al, 2021).…”
Section: What -Change Targetmentioning
confidence: 99%